Relationship Corporate Social Responsibility, Strategy on Marketing Performance: Value Creation as Mediation - Musfialdy Musfialdy; Muhammad Soim; Edison Edison (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Social investment by the company will build synergy for people, organizations, and individual which then build the company’s existence. Social investment using social capital also demands to support the company’s success in finding sustainable profits. This study aims to analyze the effect Corporate Social Responsibility (CSR) strategy on marketing performance and value creation as mediation The samples were 115 business media company in Indonesia. The data were collected by interviews and questionnaires. The data were analyzed by path analysis. The results show that CSR strategy has affected on value creation. CSR strategy affects marketing performance. Value creation has effects on marketing performance.